THE DEVELOPMENT AND USE OF SIGN LANGUAGE IN SOUTH AFRICAN SCHOOLS: THE DENIAL OF INCLUSIVE EDUCATION (African Disability Rights Yearbook, 2021)
The lobbying and advocacy predating, and litigation in Springate v Minister of Basic Education Case no 4846/2009 (PMB HC) culminated in a victory for South African deaf learners, namely, to study sign language as a language subject for matriculation in schools. This article discusses the litigation in Springate, focusing on South African sign language as a school subject, and the silence of the Pan-South African Language Board in the litigation, curriculum development and monitoring, enforcement and advocacy by relevant institutions (the South African Human Rights Commission and the Commission on the Rights of Cultural, Religious and Linguistic Communities), the media and civil society. The rationale for legislative and policy choices distinguishing between sign language as a disability right or linguistic minority right is considered, as well as litigation and law reform for the recognition and use of sign language in education and the provision of sign language interpreters in select jurisdictions. It is concluded that the protection of sign language in domestic law and policy, though fragmented, should be read within the growing acceptance globally that sign language is both a right accruing due to disability accommodations, and due to the linguistic and cultural minority status of deaf users of sign language. The current offering of sign language as a language subject in mainstream or full service schools in South Africa is considered to be constrained by the ‘reasonable practicable’ standard, contrary to the notion of full inclusive education. The continual monitoring of the linguistic and cultural rights of sign language users will hopefully address the shortcomings in the education system, but this will need dedicated funding and political will.